Lichens - Vainio, Edv. A. (Edvard August), 1853-1929. (Anvers : Impr. J.-E. Buschmann, 1903)
Cover title. Includes bibliographical references and index. Stafleu & Cowan, Taxonomic Lit., ed. 2, Mode of access: Internet.